Why the Foxconn Model Does Not Die: Production Networks and Labour Relations in the IT Industry in South China. Issue 2 (23rd February 2017) - Lüthje, Boy; Butollo, Florian
Abstract: This contribution tracks the recent geographical and structural changes in the electronics contract manufacturing (ECM) industry in China's Pearl River Delta (PRD) and the corresponding modifications in labour relations. We find that a diversified ECM industry in the PRD has been expanding in spite of rising production costs and that investments in other regions in China should therefore be seen as a complement, rather than a substitute, for production capacities in the PRD. Our investigation of working conditions at three major production sites in the PRD in May 2013 based on 167 worker interviews shows that substantial changes in employment regimes are absent and that wage rises remain modest. The industry continues to operate on the flexible employment of low-skilled and poorly paid migrant workers. We conclude that improvements of working conditions must rely on the associational power of workers and global efforts to regulate the highly competitive ECM industry.